Integrasi Kompres Hangat dalam Asuhan Keperawatan Demam Tifoid - Sukma Saini; Muhammad Nur; Ismail Ismail; Muhammad Basri; sitti Rahmatiah (Celebes Health Journal, 2025)
Background: Typhoid fever remains a major public health problem in low- and middle-income countries, including Indonesia, where incidence exceeds 500 cases per 100,000 population despite modest global declines. Pharmacological treatment is essential, but non-pharmacological nursing interventions such as warm compresses may enhance fever management and patient comfort. Objective: This study aimed to evaluate the effectiveness of warm compresses in reducing body temperature and improving comfort among hospitalized typhoid fever patients. Methods: A quasi-experimental pre-test and post-test design was conducted with 32 patients diagnosed with typhoid fever at RSUD Haji Makassar between March and June 2025. Warm compresses at 40°C were applied to the axilla, forehead, and neck for 15 minutes twice daily over three days, in addition to standard pharmacological therapy. Body temperature was measured using digital thermometers, and patient comfort was assessed with a numeric rating scale. Paired t-tests and Wilcoxon signed-rank tests were used for analysis. Results: Mean body temperature decreased significantly from 38.6°C (SD = 0.4) to 37.4°C (SD = 0.3) after intervention (t = 12.53, p < 0.001). Median comfort scores improved from 4 (IQR = 3–5) to 8 (IQR = 7–9) (Z = –4.89, p < 0.001). Conclusions: Warm compresses significantly reduced fever and enhanced comfort in typhoid fever patients, supporting their use as a complementary nursing intervention alongside pharmacological therapy.